Gambaran Tingkat Keparahan Karies Gigi Anak Sekolah Dasar di 10 Kecamatan Kabupaten Jember - Ristya Widi Endah Yani; Hestieyonini Hadnyanawati; Kiswaluyo Kiswaluyo; Zahara Meilawaty (Fakultas Kedokteran Gigi Universitas Jember, 2015)
Until todays, dental caries disease is a major problem in a child's oral cavity. Children aged 6-10 years old are vulnerable to dental and oral diseases. The aim of this study was to describe the severity of dental caries in primary school children in 10 districts in Jember. An observational study with cross sectional approach was conducted in July-September 2015. Accidental sampling was 102 children of primary school grade 1 to grade 6 in 10 districts in Jember (Ambulu, Balung, Ledokombo, Tanggul, Mayang, Gumukmas, Jenggawah, Pakusari, Rambipuji and Sukorambi). The variables studied were deciduous tooth caries with four categories of severity i.e. pulp irritation (IP), pulp hyperemia (HP), gangrene of the pulp (GP), gangrene roots (GR). Data were presented in descriptive research results with a frequency distribution table and a bar chart. The results showed that most cases of primary teeth were gangrene tooth root 626 (38.1%), subsequently gangrene dental pulp 454 (27.7%), 360 dental pulp hyperemia (21.9%), and cases of irritation of the pulp were at least 202 teeth (12.3%). The high incidence of gangrene roots caused by deciduous teeth which have a tendency to be more susceptible to the development of caries lesions, lack of knowledge, awareness and motivation of parents of the importance of maintaining oral hygiene, the transition period the child's diet between home-cooked meals with school meals, which tend to choose cariogenic foods.